A study on Lichtenstein's hartebeest, Alcelaphus lichtensteini (Peters 1849), and its habitat in south-eastern Rhodesia - Skinner, J.D. (John Dawson), 1932- (University of Pretoria, 2022)
Dissertation (MSc (Zoology))--University of Pretoria, 1980.